(untitled) (Research, Society and Development, 2023)
Structural, organizational and normative developments in the school environment in Brazil over the last fifty years suggest that the role of teachers must be considered in all social, cultural and scientific innovations that drive these changes. Thus, the objective of the present study was to analyze whether Physical Education teachers have access to information through continuing education on Badminton within the scope of the District Educational Coordination 05 (CDE05) of the State Secretariat for Education and Sports (SEDUC - AM) of the State of Amazonas, Brazil. METHODOLOGY: this is a qualitative and quantitative research, documentary research in technical documents from CDE05 and SEDUC-AM, in addition to field research that heard 30 physical education teachers from CDE05 from SEDUC-AM. The results revealed that the teacher training programs in the CDE05 of SEDUC - AM lacked significant methods and content, so it is very important to underline the value of a new approach in the teacher that aims to ensure the acquisition of essential competences in accordance with the Recommendation of the National Council of Education (CNE and the State Council of Education (CEE) and to create cooperation between the School and public schools to infer sports training in sports without great tradition in the country and in the State of Amazonas, such as Badminton. To conclude, a new approach to continuing teacher education could promote a broad advance in the specialization and professionalization of Physical Education teachers, adapting the educational path to the best practices.